PsycEXTRA Dataset 2011
DOI: 10.1037/e520602012-347
|View full text |Cite
|
Sign up to set email alerts
|

Processing Ordinality and Quantity: The Case of Developmental Dyscalculia

Abstract: In contrast to quantity processing, up to date, the nature of ordinality has received little attention from researchers despite the fact that both quantity and ordinality are embodied in numerical information. Here we ask if there are two separate core systems that lie at the foundations of numerical cognition: (1) the traditionally and well accepted numerical magnitude system but also (2) core system for representing ordinal information. We report two novel experiments of ordinal processing that explored the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…This is in clear contrast with Rubinsten and Sury (2011) who proposed that these skills represented two independent, parallel core systems. Our findings also prompt at least some reconsideration of claims about the independence of comparison and ordering skills (e.g., Goffin & Ansari, 2016;Lyons & Beilock, 2013).…”
Section: Summary Conclusion and Future Directionsmentioning
confidence: 61%
See 2 more Smart Citations
“…This is in clear contrast with Rubinsten and Sury (2011) who proposed that these skills represented two independent, parallel core systems. Our findings also prompt at least some reconsideration of claims about the independence of comparison and ordering skills (e.g., Goffin & Ansari, 2016;Lyons & Beilock, 2013).…”
Section: Summary Conclusion and Future Directionsmentioning
confidence: 61%
“…These studies most often used symbolic and non-symbolic comparison tasks. Nevertheless, recent studies (starting with Beilock, 2011, andRubinsten &Sury, 2011) also highlighted the importance of number-ordering skills in mathematical abilities. Indeed, Lyons et al (2014) showed that beyond a certain point in development, number-ordering abilities become the strongest predictors of arithmetic skills (although number comparison performance also continues to be a significant predictor).…”
Section: Summary Conclusion and Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is true of efforts to understand how the brain represents basic numerical representations, as well as research into how these basic processes underpin more sophisticated mathematical thinking. In the past few years, there has been a steady uptick in work on how we process the relative order of numbers (e.g., Brannon, ; Colomé & Noël, ; Delazer & Butterworth, ; Fias, Lammertyn, Caessens, & Orban, ; Franklin & Jonides, ; Franklin, Jonides, & Smith, ; Jou, ; Knops & Willmes, ; LeFevre & Bisanz, ; LeFevre, Kulak, & Bisanz, ; Lyons & Beilock, , , ; Lyons, Price, Vaessen, Blomert, & Ansari, ; Rubinsten & Sury, ; Turconi, Campbell, & Seron, ; Turconi & Seron, ; Zorzi, Di Bono, & Fias, ). Intriguingly, this work suggests that ordinality may be a key to understanding how we represent numbers symbolically (e.g., as Indo‐Arabic numerals; Delazer & Butterworth, ; Lyons & Beilock, , ; Turconi & Seron, ).…”
mentioning
confidence: 99%
“…Second, there might be still other tasks to be included in the screening tool. For example, the task of comparing analog quantities (34), both small and large quantities, ordering numbers (35), and transcoding tasks could be included in the screening tool. Further research can include the fMRI and eye tracking methodology to reveal the brain bases of MD.…”
Section: Discussionmentioning
confidence: 99%